Achieving early functional auditory access in paediatric cochlear implantation. - Orzan, E; Muzzi, E; Marchi, R; Falzone, C; Battelino, S; Ciciriello, E (Acta Otorhinolaryngol Ital, 2016)
Cochlear implantation (CI) is a viable option for providing access to auditory stimulation in severe-to-profound hearing loss/impairment of cochlear origin. It has been demonstrated that CI is safe and effective for deaf children. Younger age at activation after CI is linked with better outcomes. It is important to study variables and issues that can interfere with an early fitting and access to sound after CI. They range from patient characteristics, family compliance and support, to technical, medical or organisational problems. A SWOT analysis and a subsequent TOWS matrix was conducted to discuss issues and propose recommendations to be considered when operating an early switch on of the CI.